Un quotidien partagé entre clercs et laïcs : la gestion de la vie communautaire des chapitres séculiers de Coimbra d’après leurs statuts (XIVe et XVe siècles) - Campos, Maria Amélia (2020)
The medieval city of Coimbra boasted a cathedral chapter plus another seven collegiate churches with their secular clergy. The statutes of four of these churches survive from before the sixteenth century. The community life of the collegiate churches of Coimbra will be examined using these medieval normative writings. The aim is to better understand the differences and resemblances between the collegiate churches and to estimate the influence of the cathedral chapter on delimiting community life in them. These institutions having been characterised, evidence of the participation, even the interference of laypeople in church life will be brought to the fore. What role did laypeople have in local church normative? Which laypeople do documents refer exactly? Besides, were they able to influence the everyday workings of the institutions which they were linked to? Answering these questions enables a better understanding of the social, economic and spiritual organisation of a city in which these communities of secular clergy were key.